(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The artistic career of W.B.Yeats, one of the main exponents of modern British Poetry came under the powerful spell of a few women of his time, who not only made important contribution to Yeats’ poetic development but moulded his personality as well. The present article proposes to be a biographical study of some of these influences upon Yeats, based on a few well-known biographies of the poet, and a few related critical studies. Instead of broadening its perspective into the socio-political frame of the poet’s time the paper chooses to confine itself to the ebb and flow of fathomless sorrow and the pinnacle of joy experienced by a hyper-sensitive mind.